Energy Efficiency: a Strategy of Public Policy in Central America - Blanco, José María (2009)
This essay highlights the energy efficiency topic in the context of the Central American power industry, as a complement to the conventional development of the national energy system based on the construction of new power generation plants. After describing the challenges faced by the regional power sector –where Costa Rica is not the exception- to cope with the growing electricity con-sumption, the energy efficiency approach integrating the active participation of the end user is an immediate opportunity to change the current paradigm with global environmental benefits. This article explains the progress of this region in recent years based on a Public Policy Strategy on Energy Efficiency, the lessons learned till this day, as well as perspectives for a region highly dependent on imported hydrocarbons for power generation, in terms of energy savings, avoided costs, and mitigated tons of global warming gases.